Tafsir Madzhab Ahmadiyah Karya Hazrat Bashiruddin Mahmud Ahmad - Abd Majid (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2022)
In the development of the Qur'an has experienced growth in the field of methodology, orientation, style and systematics. This development is inseparable from the pace of human life in general and Muslims in particular. Each commentator has a different method and style. This difference is caused by experience, knowledge that becomes expertise. And this is the condition that can be seen from Hazrat Bashiruddin Mahmud Ahmad's leasing style in his commentary, Quranummajid. If you pay attention to the contents of the verses of the Qur'an, in general it seems that Basyiruddin did not try to present a lengthy form. Basyiruddin tried to overcome the meaning and the verses that were explained briefly and explained the boundaries without the problem of other things that happened, which was done to the verses of the Qur'an in accordance with the order in the Mushaf in the framework of an easy explanation in language. and ways that can be reached In certain cases, sometimes Basyiruddin still gives a fairly long discussion. As in the matter of Surah al-Fatihah and the problem of prophethood.